2023
DOI: 10.1186/s12957-023-02888-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of non-sentinel lymph node metastasis in breast cancer with 1–2 sentinel lymph node macrometastases underwent total mastectomy: a case-control study

Abstract: Background The randomized trials which include ACOSOG Z0011 and IBCSG 23-01 had found that the survival rates were not different in patients with cT1/2N0 and 1–2 sentinel lymph node (SLN)-positive, macro/micrometastases who underwent breast-conserving therapy, and micrometastases who underwent total mastectomy (TM), when axillary lymph node dissection (ALND) was omitted. However, for patients with cT1/2N0 and 1–2 SLN macrometastases who underwent TM; there was still insufficient evidence from c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Duplicate studies accounted for 516 of these exclusions, whereas screening titles and abstracts resulted in another 1114 exclusions. The full texts of 125 articles were evaluated and 25 studies met the inclusion criteria [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Duplicate studies accounted for 516 of these exclusions, whereas screening titles and abstracts resulted in another 1114 exclusions. The full texts of 125 articles were evaluated and 25 studies met the inclusion criteria [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 summarizes the findings of the meta-analysis. Three studies examined tumor localization (upper outer quadrant) as a factor [ 15 , 19 , 26 ]; however, one study [ 26 ] reported an error in the 95 % CI [1.506, 0.121], and another study [ 15 ] did not report OR values or 95 % CI. Therefore, the number of exposed and unexposed patients in the case and control groups of the three studies were merged.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations